Effects of Lactiplantibacillus plantarum and Fermentation Time on the Quality, Bacterial Community, and Functional Prediction of Silage from Lotus corniculatus L. in Karst Regions - Yang Wang; Yang Yang; Xiaoyu Yang; Lei Huang; Puchang Wang; Lili Zhao (Agriculture)
Abstract: To improve the silage quality of Lotus corniculatus L. and expedite the promotion of cultivated varieties, this study investigates the impact of Lactiplantibacillus plantarum on the fermentation characteristics, bacterial community, and functional aspects of silage. The experiment included a control (CK) and a Lactiplantibacillus plantarum (LP) treatment, with sampling conducted at 3, 7, 15, and 45 days of fermentation to monitor nutritional value and fermentation quality, as well as changes in the bacterial community at 3 and 45 days. The results indicated that compared to the CK, the addition of LP significantly increased the lactic acid, dry matter, and crude protein content (p < 0.05) while substantially decreasing the water-soluble carbohydrates, pH, NH3-N, and acetic acid levels (p < 0.05). And the effect of adding LP was the most significant after 45 days of fermentation. LP promoted the growth of beneficial bacteria and inhibited harmful bacteria, with LP becoming the predominant genus and species after 45 days of fermentation. The metabolic pathway analysis revealed that the addition of LP enhanced carbohydrate metabolism and improved the replication and repair, translation, transcription, and membrane transport functions of the bacterial community. In summary, the addition of LP significantly enhances the silage quality of L. corniculatus and may serve as an effective method for promoting the application of L. corniculatus in karst regions.